SMART INTEGRATION OF UKRAINE’S ENERGY SYSTEM INTO THE SINGLE ENERGY MARKET OF THE EU: CHALLENGES AND PROSPECTS - ZVARYCH, Roman; KHARKOVSKYI, Bohdan (Journal of European Economy, 2025)
This article is devoted to analyzing the process of Ukraine’s energy market integration into the single energy space of the European Union. It examines the current state of this integration, key challenges, and future prospects. A comprehensive methodological approach was employed, including a comparative analysis and, for the first time, a SWOT analysis, to identify the Ukrainian energy system’s strengths, weaknesses, development opportunities, and threats— particularly those arising from military actions and environmental challenges. Special focus is placed on the synchronization of the Ukrainian power system with Europe’s ENTSO-E grid, its modernization, and implementation of new technologies, which create new opportunities for electricity exports and imports as well as for attracting international investment. A Pearson correlation analysis was also conducted for the first time to evaluate electricity import volumes and their impact on the country’s energy security. The study concludes that for Ukraine to achieve full integration with the EU energy market, it must implement extensive technological modernization, expand international partnerships, harmonize its legislation, and adopt new environmental standards. JEL: F15, Q40, Q48, Q58, O38.